Development of Speech and Communication in Polish Children with 22q11.2 Deletion Syndrome: A Cross-Sectional Study - Natalia Moćko; Marcin Rudzki; Zuzanna Miodońska; Julia Olesiak; Katarzyna Jochymczyk-Woźniak; Michał Kręcichwost (Brain Sciences)
Background/Objectives: 22q11.2 microdeletion syndrome (22q11DS) is a genetic disease caused by aberration of chromosome 22 that results in some phenotypic features and developmental disorders. This paper presents a cross-sectional study on speech and communication of Polish children with 22q11DS. Methods: Individuals affected with 22q11DS may show difficulties in functioning, including speech and hearing. Therefore, we prepared a speech development questionnaire and employed it to obtain data from parents (or legal guardians) of 54 children with 22q11DS. The questionnaire covered the following speech and communication development stages: babbling, using first words, first sentences, verbal and non-verbal communication, speech disfluencies, hearing loss, speech intelligibility, difficulties in interpersonal contact, and participation in speech therapy. The obtained answers underwent statistical analysis to verify relationships between the stages of personal development and selected dysfunctions and disorders. Results: In the study group we observed delays in achieving subsequent speech developmental stages and that hearing loss was associated with delays in producing first words. Hearing loss was reported in about a quarter of cases, but a significant proportion of children (55.56%) reported speech disfluencies, which had not been emphasized in previous works, where hearing loss is considered a common co-occurring disorder. Conclusions: Our findings suggest that this may represent a phenomenon associated with 22q11DS that warrants further investigation using standardized tests for assessing disfluencies. Additionally, we observed that speech therapists and caregivers were perceived as not fully aware of the speech development impairments caused by 22q11DS. These preliminary observations point to the need for future studies and increased awareness efforts in this area.